Adapting to heat-health vulnerability in temperate climates: current adaptation and mitigation responses and future predictions in Aotearoa New Zealand - Muhamad, Siti Nurfahirah; Mohd Shabri, Nur Shabrina Azreen; Cotter, James David; Bolton, Annette (De Gruyter Open, 2024)
Climate change is raising global temperatures, leading to more extreme heat events, even in temperate climates like Aotearoa|New Zealand (A|NZ). The impact of rising temperatures and the adequacy of planning measures remain underexplored. This paper highlights A|NZ’s anticipated heat-health challenges by analyzing vulnerable populations and assessing current response systems, thereby reinforcing the need for system-level redress, mitigation and adaptation. A scoping review examined the impact of heat and existing mitigation and adaptation responses for vulnerable populations in temperate regions, with a focus on A|NZ. Additionally, temperature trend analysis was conducted for current and projected trends using Climate CHIP for six major heat-affected cities in A|NZ to assess the recognition of heat as a societal concern.